Friction stir welding of 25%SiC/2124Al composite with optimal mechanical properties and minimal tool wear. (18th August 2017) - Fernández, R.; Ibáñez, J.; Cioffi, F.; Verdera, D.; González-Doncel, G.
ABSTRACT: In this research, 8-mm-thick plates of 25%SiC/2124Al composite have been joined successfully by using an un-threaded WC–Co tool which showed minimal tool wear. Decreasing the rotational and advancing speeds is a key factor to obtain successful joints. Defect-free welds, and a joint efficiency (100UTSjoint /UTSBaseMaterial ) of up to 97%, can be achieved if a high forge force, Fz, (above some 15 kN) is reached. Proportionality between the torque, M, and Fz is observed. High Fz values, and corresponding M, lead to high values of the total energy per unit length of weld, H tot, supplied by the tool to the workpiece. It is proposed that most of this energy is spent in plastic deformation of the high strength composite.